Comparison between effectiveness of sublingual misoprostol and intracervical dinoprostone gel for induction of labour in pregnant women - Das, Dhira; Medhi, Robin; Chowdhury, Nilanjan (International Journal of Research in Medical Sciences, 2023)
Background: This hospital-based, prospective, comparative interventional study aimed to compare the effectiveness of sublingual misoprostol and intracervical dinoprostone gel for induction of labor in primigravida women. Methods: A total of 100 patients were alternately assigned to induction with either Misoprostol 25mcg 6 hourly or dinoprostone Gel 0.5mg 6 hourly. Results: The induction delivery interval was significantly longer in the dinoprostone group compared to the misoprostol group. The incidence of fetal distress was slightly higher in the Dinoprostone group, but the difference was not statistically significant. There were no significant differences between the two groups in the incidence of respiratory distress, birth asphyxia, and APGAR 1 MIN <6. Conclusions: This study suggests that sublingual misoprostol (a type of prostaglandin E1, or PGE1) is more effective than intracervical dinoprostone gel (a type of prostaglandin E2, or PGE2) for cervical ripening and induction of labor.